Idolatry and the colonial idea of India - Ganguly, Swagato, author.
1 online resource (208 pages)
Keywords: "This book explores literary and scholarly representations of India from the 18th to the early 20th centuries in South Asia and the West with idolatry as a point of entry. It charts the intellectual horizon within which the colonial idea of India was framed, tracing sources and genealogies which inform even contemporary descriptions of the subcontinent. Using idolatry as a concept-metaphor, the book traverses an ambitious path through the works of William Jones, James Mill, Friedrich Max Mueller, John Ruskin, Alice Perrin, E. M. Forster, Rammohan Roy and Bankimchandra Chatterjee. It reveals how religion and paganism, history and literature, oriental thought and western metaphysics, and social reform and education were unfolded and debated by them. The author underlines how idolatry, irrationality and social disorder came to be linked by discourses informed by Enlightenment, missionary rhetoric and colonial reason. This book will appeal to scholars and researchers in history, anthropology, literature, culture studies, philosophy, religion, sociology and South Asian studies as also anyone interested in colonial studies and histories of the Enlightenment."--Provided by publisher.